EVALUATION OF EPIDERMAL GROWTH FACTOR RECEPTOR (EGFR) EXPRESSION IN UROTHELIAL CARCINOMA: A POSSIBLE PROGNOSTIC ROLE - Basharat, Shifa; Ayesha Sajjad; Faryal Javaid; Maria Khan; Maria Tasneem Khattak; Iqbal Muhammad Khan (Journal of Ayub Medical College Abbottabad, 2024)
Background: Urothelial carcinoma is a subtype of urinary bladder cancer which carries a higher morbidity and mortality worldwide. It is estimated that 90% of the patients presenting to the hospitals with history of bladder cancer are diagnosed with urothelial carcinomas. Objective of the study was to evaluate the strength of EGFR expression and its prognostic role in urothelial carcinoma. It was a cross-sectional study conducted at the Rehman Medical Institute Peshawar from July 2022 to February 2023. Methods: A total of 98 specimens of patients diagnosed with urothelial carcinoma were examined in histopathology department. Patients with other malignancies were excluded. Demographic characteristics of participants, tumour grading, invasion of the surrounding structures and EGFR expression was recorded, and data analysis was performed with SPSS-23. Results: Mean age of the participants was 58.68±8.61 years. Gender distribution revealed 67(68.4%) males and 31(31.6%) females with a male to female ratio of 2.1:1. A total of 61 (62.2%) patients exhibited low grade of urothelial carcinoma while 37(37.8%) patients showed high grade malignancy. Expression of EGFR was not observed in 04 (4.1%) specimens while 62(63.3%) specimens revealed weak to moderate expression and 32(32.7%) showed strong expression of EGFR. Out of 61 patients with low grade of tumour, 04 (6.6%) patients exhibited no expression, 50(80%) patients exhibited weak to moderate expression and 07(11.5%) patients revealed strong expression of EGFR. Out of 37 patients with high tumour grade, 12(32.4%) revealed weak to moderate and 25 (67.6%) revealed strong expression of EGFR. Higher tumour grades and tumours with deeper penetration revealed a strong expression of EGFR with a p-value of <0.001. Conclusion: Strong expression of EGFR in tumours with higher grade validates its prognostic role and can be utilized for targeted therapy with potentially lifesaving consequences in patients presenting with urothelial carcinoma.